Юридична природа та перспективи використання приміток у Кримінальному кодексі України - Тростюк, З.А. (Часопис Київського університету права, 2009)
В статье рассматриваются проблемы юридической природы примечаний статей Особенной части Уголовного кодекса Украины, перспектив их дальнейшего использования. Предложена классификация примечаний и пути усовершенствования законодательства об уголовной ответственности. Ключевые слова: Криминальный кодекс Украины, Особенная часть, примечания статей, законодательная техника. The problems of legal nature of notes of reasons of Special part of the Criminal code of Ukraine are examined in the article, prospects of their further use. Classification of notes and way of improvement of legislation is offered about criminal responsibility. Key words: Criminal Code of Ukraine, Special part, notes of articles, legislation’s technique.